Tauhid dalam Perspektif Tasawuf - Said Aqiel Siradj (Islamica: Jurnal Studi Keislaman, 2010)
This paper is aimed at articulating the Sufi concept of tawhid, God unity. Tawhid has always been an intriguing issue to tackle within the premises of tasawuf considering that it is this notion that has triggered controversies over centuries. The Sufis have often been accused of betraying Islam by presenting a distorted version of tawhid. This paper will neutralize this accusation and contend that the Sufistic concept of tawhid is categorically Islamic, Qur?anic and prophetic. Against all odds, tasawuf has survived from all sorts of onslaught. This means that tasawuf is just in line with the prophetic Islam, or else with the pure of Islam brought about the prophet Muhammad. The paper will consult the views of many leading Sufis to support its basic contention. The strength of this paper does not indeed lie in its basic premises, but in its data, line of argument and in its analysis. The paper will leave aside for the time being the views of the Sufis that belong to the periphery.